Effects of Detailing and Fibers on the Static and Blast Behaviour of High‐Strength Concrete Beams - Charles, Charlemagne Junior (Université d'Ottawa / University of Ottawa, 2019)
The CSA S850 Blast standard provides guidelines that can be used to enhance the blast performance of reinforced concrete structures. In the case of beams, the standard requires the use of top continuity (compression) bars and well-detailed transverse steel to ensure strength and ductility under blast loads. However, the requirements in the CSA S850 standard are intended for normal-strength concrete structures. Given the increased use of high-strength concrete (HSC) in practice, there is a need to explore the effects of modern blast designs on the behavior of HSC structures subjected to blast loads. Accordingly, this project examines the effect of modern reinforcement detailing on the static, dynamic and post-blast performance of high-strength concrete beams. The study further examines the ability to use fibers to relax such detailing and simplify construction. A total of seventeen beams are tested. Static testing is conducted under four-point bending, with blast testing conducted using the University of Ottawa shock-tube. The post-blast behavior of the beams is assessed by conducting residual static tests on the blast-damaged specimens. The parameters investigated include the effects of: blast detailing vs. nominal detailing, steel fibers, the effect of longitudinal steel ratio (in compression and tension) and tie spacing. The results show that under static loads, the use of blast detailing significantly improves the flexural behavior of the beams in terms of ductility. Likewise, the provision of continuity (compression) bars and closely spaced ties is found to improve blast performance by better controlling displacements, increasing blast resistance, limiting damages and allowing for important post-blast residual capacity. The use of steel fibers and relaxed detailing (increased tie spacing) is found to increase resistance and improve cracking behavior under static loads, with an ability to match the blast performance of more heavily-detailed HSC specimens. The use of fibers also allowed for substantial post-blast capacity. Finally, the steel ratio (in tension, in compression and in the transverse direction) was found to affect the blast behavior of the HSC beams. In addition to the experiments, the analytical study predicts the static and blast response of the tested beams using sectional analysis and non-linear SDOF modeling. Results show that the analysis methodology was able to predict the static and blast responses of the blast-detailed and fiber-reinforced HSC beams with reasonable accuracy.
Keywords: Blast detailing; Fiber-reinforced concrete; High strength concrete; Steel fiber; Static; Dynamic; Residual; Shock-tube; Dynamic analysis; SDOF